Национально-этнические объединения Крыма как субъекты гражданского общества (на примере Крымского республиканского общества болгар им. Паисия Хилендарского) - Узунова, Л.В. (Культура народов Причерноморья, 2013)
В данной статье автор публикует результаты диссертационных исследований деятельности национально-этнических объединений Крыма, в частности, Крымского республиканского общества болгар имени П.Хилендарского,исследует историю вопроса развития межнационального движения в Крыму на основании создающейся в независимой Украине национально-культурной политики. Автор статьи подчеркивает , что многие формы и виды деятельности общества крымских болгар характерны для всех национально-этнических объединений Крыма,несмотря на разный уровень их развития и функционирования. В результате исследования автор приходит к выводу,что созданная в Украине законодательная база в области национально-культурной политики способствует созданию благоприятных условий для образования и развития национально-этнических объединений в АРК, как специфических субъектов гражданского общества. В цій статті авторка публікує висновки дисертаційного дослідження діяльності національно-етнічних товариств Криму,зокрема, Кримського республіканського товариства болгар ім.П.Хілендарського, досліджує історію питання розвитку міжнаціонального руху в Криму на базі нової в незалежній Україні національно-культурної політики, Авторка підкреслює, що різноманітні форми та види діяльності товариства кримських болгар притаманні для всіх національно-етнічних товариств Криму, незалежно від їх рівня розвитку та функціювання. Авторка робить висновок,що розроблена в незалежній Україні національна-культурна політика сприяє розвитку дяльності національно- культурних товариств АРК, як субєктів цивільного суспільства. In this article, the author publishes the results of dissertational researches of ethnic associations in particular, Crimea, Crimean republican society of Bulgarians p. Hilendarski, explores the history of the development of international traffic in the Crimea on the basis created in the independent Ukraine national cultural policy. The author stresses that many of the forms and types of activity of the Crimean Bulgarians are common to all ethnic groups in Crimea, in spite of their different level of development and operation. As a result of the study, the author concludes that 1. the legislative framework created in Ukraine in the field of national cultural policy helps to create favourable conditions for the education and development of ethnic groups in Crimea, as specific actors in civil society. 2. the activities of ethnic groups, particularly the Crimean republican society of Bulgarians. P. Hilendarski: participation in public, political and economic life of Crimea, the Crimean population of socially significant events, international, ètnokonfessional′nogo and international dialogue to raise national awareness of citizens, based on universal values, work with students in terms of socialization for contemporary young generation – affirms the fact that Bulgarian society (as well as all national and ethnic associations of Crimea) acts as a full subject of civil society and promotes the formation of civic culture, ethnic harmony, tolerance – important prerequisites for the development of civil society in the Crimea.